2006
DOI: 10.1167/iovs.05-1376
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cholinergic and Dopaminergic Amacrine Cells in Streptozotocin-Diabetic Rat and Ins2Akita-Diabetic Mouse Retinas

Abstract: Dopaminergic and cholinergic amacrine cells are lost during the early stages of retinal neuropathy in diabetes. Loss of these neurons may play a critical role in the development of visual deficits in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
186
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(200 citation statements)
references
References 46 publications
8
186
0
6
Order By: Relevance
“…Immunohistochemistry was performed for CM-1, a marker for the activated form of caspase-3, which only appears in cells undergoing apoptosis. The study revealed a similar magnitude increase in CM-1 positive cells compared to that measured by TUNEL [1]. Many of the CM-1 positive cells appeared spatially distinct from blood vessels, which were identified by immunoreactivity for a vascular basement membrane protein called agrin, which is abundant in the retinal vasculature [19].…”
Section: The Retinal Cell Death Involves Several Types Of Neuronssupporting
confidence: 60%
“…Immunohistochemistry was performed for CM-1, a marker for the activated form of caspase-3, which only appears in cells undergoing apoptosis. The study revealed a similar magnitude increase in CM-1 positive cells compared to that measured by TUNEL [1]. Many of the CM-1 positive cells appeared spatially distinct from blood vessels, which were identified by immunoreactivity for a vascular basement membrane protein called agrin, which is abundant in the retinal vasculature [19].…”
Section: The Retinal Cell Death Involves Several Types Of Neuronssupporting
confidence: 60%
“…The obvious question to ask here is whether the transient coexpression of these two neurofilament proteins not only stabilizes the dendrites of starburst amacrines and ganglion cells but also somehow promotes their mutual recognition. In the long term we are aiming to clarify whether the expression of different combinations of neurofilament proteins in the retina has anything to do with the selective vulnerability of certain of the neuronal classes which, for example, has been observed during diabetic retinopathy (Park et al, 2003b;Gastinger et al, 2006;Kern and Barber, 2008).…”
Section: "Starburst" Amacrine Cellsmentioning
confidence: 99%
“…A similar approach could be applied to other retinal diseases, particularly those with known cell-based dysfunctions. There is accumulating evidence that diabetic retinopathy compromises distinct components of the neurovascular unit, such as astrocytes, pericytes, and cholinergic amacrine cells [54,56]; optogenetics could target these cells to supplement their health and function.…”
Section: Resultsmentioning
confidence: 99%